Arab Saudi dan Iran: Kontestasi Ideologi dan Dampaknya di Kawasan Timur Tengah Pasca The Arab Spring - Hamid, Ihsan; Setiadi, Ozi (State Islamic Institute of Kudus (IAIN Kudus), 2021)
Saudi Arabia and Iran: Ideological Contest and Its Impact in the Middle East Region after The Arab Spring. Tensions surround the Middle East region, especially between Saudi Arabia and Iran. The Sunni-Shia ideological factor contributed to the conflict in the region and also attracted these two countries. This research will answer the question how is the form of contestation of Sunni-Shia ideology represented by Saudi Arabia with Iran in the Middle East? What are the factors and impacts of the conflict between Saudi Arabia and Iran on countries in the region after the Arab Spring? The historical approach (historical analysis) was chosen to explain the two research questions above, using qualitative methods. Saudi Arabia and Iran represent both a Sunni-Shia ideological contestation, both of which try to support each other's ruling government, as well as conflicting oppositions based on ideological backgrounds. This support is carried out in the form of military assistance, weapons, or direct involvement which is marked by various statements that appear in the media. The disharmony of Saudi Arabia and Iran is driven by several factors, namely first, the Sunni-Shia ideological struggle between the two. Second, the claim to be the holder of the Islamic religion in each version. And third, oil. While the impact of this is political instability in the Middle East region after the Arab Spring, to the